Plant Invasion in the Minds of Students of Selected Secondary Grammar Schools - Florianová, Anna (Scientia in educatione, 2015)
The aim of this study was to evaluate the knowledge and perception of invasive plants of secondary grammar school students. The questionnaire survey showed that students’ knowledge is generally very weak; nearly one fifth of them never heard about plant invasions, more than half of them answered less than half of the questions. A question on particular invasive species was the most problematic one. School appears to be the most important source of information about invasive plants. It is therefore important to recommend the teachers to focus more on plant invasions.